Neutrinos and implications for physics beyond the standard model - Shrock, R. (Singapore World Scientific, 2003)
This important book presents the proceedings of the conference "Neutrinos and Implications for Physics Beyond the Standard Model", put on by the Yang Institute for Theoretical Physics, State University of New York at Stony Brook.
Includes bibliographical references and index
Keywords: Cơ bản